Penerapan Teknologi Augmented Reality Katalog Perumahan Sebagai Media Pemasaran Pada PT. San Esha Arthamas - Fernando, Yusra; Ahmad, Imam; Azmi, Arief; Borman, Rohmat Indra (STIKOM Tunas Bangsa Pematangsiantar, 2021)
PT. San Esha Arthamas is a company engaged in the sale of housing. In marketing its products other than social media, the company uses a housing catalog in the form of a book. However, with this method, people feel confused and less interested in knowing and looking at the products offered. To assist in marketing, the product to be attractive, the housing catalog augmented reality (AR) technology was developed as a marketing medium. AR is a technology that can combine real and virtual objects in 3D in realtime. This research produces an application that can display the types of houses and can perform marker scans by pointing the smartphone camera at the catologist book from various angles including: top, left and right side and back. In addition, users can see interior, exterior, can zoom in, zoom out and rotate. Based on the questionnaire, it shows that the application has an impact in helping marketing with the results that 93% of respondents said they